Analysis on the Susceptibility Genes in Two Chinese Pedigrees with Familial Parkinson's Disease - Changshui Xu; Jun Xu; Yanmin Zhang; Jianjun Ma; Hideshi Kawakami; Hirofumi Maruyama; Masaki Kamada (Neurology Research International)
Objective. To screen the susceptibility genes in Chinese pedigrees with early-onset familial Parkinson's disease (FPD). Methods. Fifty-one genomic DNA samples extracted from two Chinese pedigrees with FPD, the alpha-synuclein genes (SNCA), the leucine-rich repeat kinase 2(LRRK2), PINK1(PTEN-induced putative kinase 1), PARK7(Protein DJ1), PARK2(Parkinson juvenile disease protein 2), the glucocerebrosidase (GBA), and ATP(Ezrin-binding protein PACE-1), were sequenced by the use of polymerase chain reaction (PCR) technique. The gene dose of SNCA was checked. Results. There were only two missense mutations observed, respectively, at exon 5 of LRRK2 and exon 10 of PARK2, and both were enrolled in SNPs. Conclusion. No meaningful mutations could be detected, and other susceptibility genes should be detected in FDP patients in China.